Association between functional candidate genes and organoleptic meat traits in intensively-fed beef. (September 2015) - Avilés, C.; Peña, F.; Polvillo, O.; Barahona, M.; Campo, M.M.; Sañudo, C.; Juárez, M.; Horcada, A.; Alcalde, M.J.; Molina, A.
Abstract: The aim of this study was to assess the associations between the single nucleotide polymorphisms in CAPN1, CAST, DGAT1, FABP4, LEP, RORC and SCD1 genes and the sensory meat quality in an intensively fed commercial population (Charolais, Limousin and Retinta breed). This work carried out analyses on a common Spanish population and evaluated the association between the markers and sensory traits. A total of 161 bulls were allocated to two different feedlots with two different finishing diets. Steaks aged for 7 and 21 days were assessed by both untrained and trained sensory panels. A significant association and allelic substitution effect were observed for markers UoG-CAST, LEP: g.73C > T and SCD1: g.878T > C on different descriptors evaluated by a consumer panel (tenderness and overall acceptability). There are no precedents of these kinds of association studies in a Spanish commercial population. The study suggested that CAST, LEP and SCD1 genes have a potential effect on the different measurements of sensory meat quality. Highlights: The links between functional genes and the sensory meat quality were evaluated. One hundred sixty one bulls fed with two different finishing diets were assessed. Untrained and trained sensory panels evaluated steaks aged for 7 and 21 days. A significant link was observed between CAST, LEP and SCD1 genes and sensory traits.